Analysis of Entertainment and Restaurant Tax Revenue Supervision at Regional Income Department Medan City - Pandapotan Ritonga (AIBPM Publisher, 2021)
Taxes entertainment, restaurant tax is one of a very large tax increase tax revenue role in Urban Terrain. With the development of an increasingly modern era, from year to year more and more entertainment venues and restaurants are built in the city of Medan. Then with such conditions, what about the revenue target, and how is the supervision carried out by the Medan City Revenue Service in maximizing its revenue. This study aims to analyze how the supervision of entertainment tax revenues and restaurant taxes is carried out by the Medan City Revenue Service. This research was conducted at the Medan City Revenue Service, which is located at Jalan Abdul Haris Nasution No. 32 Medan Johor. This research is planned from May 2016 to August 2016 . The variables in this study are entertainment tax, restaurant tax and tax revenue control through the effectiveness of tax revenue. The data were analyzed descriptively quantitatively. Results of the analysis showed p engawasan entertainment tax on Regional Revenue Office Medan is still less effective with less than 80% effectiveness . Entertainment and Restaurant tax revenue in the city of Medan has not reached the predetermined target caused by the lack of awareness of taxpayers in paying their taxes and the lack of supervision of tax receipts by tax officials and related agencies.